Dutch Validation of the Self-Evaluation of Negative Symptoms Scale (SNS) - Tim van Brouwershaven; Anika Poppe; Gerdina Hendrika Maria Pijnenborg; André Aleman; Nynke Boonstra; Shiral Gangadin; Sonia Dollfus; Wim Veling; Stynke Castelein; Jan Alexander de Vos; Edith Liemburg; PHAMOUS-researchers; et al. (Brain Sciences)
Background/objectives: Negative symptoms in schizophrenia spectrum disorders are related to impaired social functioning and lower quality of life, making accurate assessment important. To date, most tools for assessing negative symptoms are observational, which can be influenced by the raters’ experience and opinion. Self-rating scales, like the Self-Evaluation of Negative Symptoms (SNS), could complement observer ratings by adding information from the patient’s perspective. Here, we aim to evaluate the psychometric properties of the Dutch translation of the SNS and the relationship between the SNS and functional outcomes. Methods: The SNS was added to the Pharmacotherapy Monitoring Outcome Survey (PHAMOUS)-protocol for adults with a DSM-5 classification of a disorder in the psychosis spectrum. Internal consistency was assessed by Cronbach’s alpha. Confirmatory factor analysis (CFA) was used to evaluate the construct validity of the five subscales of the SNS. Correlational analyses were performed between the SNS and the Positive and Negative Syndrome Scale (PANSS), the Health of Nation Outcomes Scales (HoNOS), the Global Assessment of Functioning (GAF), Functional Remission tool (FR) and the Manchester Short Assessment of Quality of Life (ManSA). Results: A total of 247 patients participated in this study. Internal consistency was good (α = 0.87). CFA confirmed the five-factor structure of the SNS. The SNS was significantly correlated (all p < 0.001) with the PANSS positive (r = 0.31), PANSS negative (r = 0.33), HoNOS (r = 0.37), FR (r = 0.27) and the ManSA (r = −0.40). Conclusions: The Dutch SNS shows good psychometric properties and is related to functional outcomes and quality of life. The SNS can be valuable in complementing current observational-based instruments, and future research may investigate whether the SNS can be used as a standalone measurement tool for the assessment of negative symptoms.